2002
DOI: 10.1046/j.1365-201x.2002.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibre type, efficiency, and mechanical optima affect freely chosen pedal rate during cycling

Abstract: Subjects with high percentage MHC I chose high pedal rates close to the pedal rates at which maximum peak crank power occurred, while subjects with low percentage MHC I tended to choose lower pedal rates, favouring high efficiency. Nevertheless, the considerable variation in freely chosen pedal rate between subjects was neither fully accounted for by percentage MHC I nor by leg strength and power. Previously recognized relationships between percentage Type I ( approximately %MHC I) and efficiency as well as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
4
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 33 publications
7
114
4
3
Order By: Relevance
“…Ideas emanating from the approaches presented in this review might aid the understanding of the correspondence between experimental task constraints and individual, behavioural, and functional settings outside the laboratory. Another observation in this context is that athletes tend to self-select strategies closely related to their natural disposition for exercise [18]. Hence, the behavioural process of pacing can vary between athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideas emanating from the approaches presented in this review might aid the understanding of the correspondence between experimental task constraints and individual, behavioural, and functional settings outside the laboratory. Another observation in this context is that athletes tend to self-select strategies closely related to their natural disposition for exercise [18]. Hence, the behavioural process of pacing can vary between athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown how performance and pacing are related [7][8][9][10], how self-paced performances involve predetermined exercise templates [10][11][12][13][14], and how pacing strategies can be predicted based on theoretical modelling [10,[15][16][17]. It has been found that athletes tend to self-select strategies closely related to their natural disposition for exercise [18] and that forced adoption of an externally paced intensity is more physically demanding compared to self-pacing [14]. To identify underlying mechanisms that are relevant in the regulation of an athlete's exercise intensity, the current review considered both pacing and decision-making literature in the context of the potential roles of perception and action in the regulation of exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Fibre-type distribution, UCP3 protein content and CS activity Fibre-type distribution was determined by electrophoresis as different isotypes of myosin heavy chain (MHC) I, MHC II and MHC IIx as previously described [32]. UCP3 was determined in fourteen participants (type 2 diabetes n=6, control n=8).…”
Section: Mitochondrial Ros Releasementioning
confidence: 99%
“…The mechanisms explaining this finding are unknown, though some have been suggested. For example, it has been shown that type I muscle fibres are more efficient than type II fibres when performing exercise at a given power output during submaximal exercise (Coyle et al 1992;Hansen et al 2002;Krustrup et al 2008;Mogensen et al 2006). An increase in the strength of type I fibres may delay activation of the less economical type II fibres, resulting in a higher power output at 2 mmol·l…”
Section: Paragraph Number 30mentioning
confidence: 99%